GAMBARAN PELAYANAN PERAWAT HEMODIALISA DI MASA PANDEMI COVID-19 DI INDONESIA TAHUN 2021 - Melati, Nimsi; Yekholya, Indri; Natanael, Natanael; Omega, Nova; Kondo, Yovita (Universitas Tribhuwana Tunggadewi, 2022)
Chronic Kidney Failure (CKD) is a disease that has a high incidence in Indonesia. End-stage CKD conditions require hemodialysis therapy at least 1-2 times every week with the help of HD nurses. The second explosion of Covid-19 cases occurred in the middle of 2021 affecting condition of nurses. Preliminary studies show that there is a difference in the care provided by nurses during pandemi. The purpose of this study was to find out description of hemodialysis nurse services during Covid-19 pandemi in Indonesia. Research method was qualitative design with a phenomenological approach. Sampling technique was purposive sampling. Population in this study were hemodialysis nurses. Sample of this study was 5 participants who came from various type B private hospitals. Results of this study are 4 themes: HD services are carried out with strict health protocols and special HD device care, limited duration of communication bring dissatisfaction for nurses and patients, nurses always prepare themselves mentally and physically before working, hope for the passing of the pandemi, patient honesty and adequate manpower are the main things for nurses. Conclusion: hemodialysis nurse services during covid-19 pandemi have been carried out with strict health protocols and nurse readiness is better at this time.